Multiple perspectives accountability systems: A perspective from Vermont - Amy Fowler (Education Policy Analysis Archives, 2018)
In response to Bae’s (2018) Redesigning systems of school accountability: A multiple measures approach to accountability and support, this commentary expands on some key considerations for states and school districts as they seek different ways to support school improvement while also addressing the competing demands of educators, policymakers, and the public. Using examples from Vermont, the author highlights the need for: (1) states and districts to make accountability part of their core statement of values, with a focus on why certain measures are selected, not what measures are selected; and (2) reciprocal accountability through better collaborations between federal, state and local actors to identify and fund the best investments for education.